Production of abnormal prothrombin (des-γ-carboxyprothrombin) by hepatocellular carcinoma: a clinical experimental study - OKUDA, H; OBATA, H; NAKANISHI, T; FURUKAWA, R; HASHIMOTO, E (Journal of hepatology, 1987)
We measured plasma abnormal prothrombin (des-gamma-carboxy prothrombin; DCP) levels in normal subjects and in patients with hepatocellular carcinoma and other various diseases using the enzyme-linked immunosorbent assay developed by Motohara et al. (Pediatr Res 1985; 19: 354-357). Fifty-eight percent of 52 patients with hepatocellular carcinoma had elevated DCP levels; 24 of 28 patients with advanced or moderately advanced hepatocellular carcinoma were positive. By contrast, 50 normal controls, 13 pregnant women and 10 patients with acute hepatitis had normal levels. Three of 55 patients with chronic liver disease, and 6 of 32 patients with other malignancies, showed a slight increase. Thus, increased plasma DCP appears useful for the diagnosis of hepatocellular carcinoma. To elucidate the mechanism for the increase of DCP in hepatocellular carcinoma, we cultured a human hepatoma cell line, huH-2, and measured the levels of this abnormal prothrombin in the medium. The huH-2 cells produced large amounts of DCP in the medium without added vitamin K. It increased in a cell concentration- and time-dependent fashion. These cells produced no detectable amount of DCP in the medium with added vitamin K. Thus, human hepatoma cell line huH-2 produces DCP, and its production is dependent on the amount of vitamin K available in the medium. Des-gamma-carboxy prothrombin may be a useful tumor marker for the diagnosis of hepatocellular carcinoma.